The twisted muse musicians and their music in the Third Reich - Kater, Michael H., 1937- (Oxford University Press, 1997)
Is music removed from politics? To what ends can music and musicians be put? In short, when human rights are grossly abused and politics turned to fascist demagoguery, can art and artists be innocent? These questions are explored in Michael Kater's survey of musicians and the music they composed and performed during the Third Reich.